2021
DOI: 10.1177/15280837211064937
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on crystallinity and mechanical properties of flexible structures 3D printed with fused deposition modeling

Abstract: Fused Deposition Modeling (FDM) is a widely used 3D printing technique, which works based on the principle of melted polymer extrusion through nozzle(s) and depositing them on a build plate layer by layer. However, products manufactured with this method lack proper mechanical strength. In this work, 2/1 twill weave fabric structures are 3D printed using poly (lactic) acid (PLA). The ultimate tensile strength in the warp and weft directions and the modulus (stiffnesses) are measured for non-heat-treated (NHT) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The reported results suggested that there are contradictions and low reproducibility of the results with the previously reported data. Jayswal and Adanur [ 22 ] demonstrated the improved mechanical properties of PLA for textile applications by using a post-heat treatment technique. Furthermore, more crystallinity was found in the case of heat-treated samples compared to samples of non-heat-treated (NHT).…”
Section: Introductionmentioning
confidence: 99%
“…The reported results suggested that there are contradictions and low reproducibility of the results with the previously reported data. Jayswal and Adanur [ 22 ] demonstrated the improved mechanical properties of PLA for textile applications by using a post-heat treatment technique. Furthermore, more crystallinity was found in the case of heat-treated samples compared to samples of non-heat-treated (NHT).…”
Section: Introductionmentioning
confidence: 99%
“…38,39 It has been extensively used in pharmaceutical and biomedical applications, 40 electrochemical energy conversion and storage, 41 packaging and tissue engineering, 42 fabric and fashion industries. 14,4345…”
Section: Methodsmentioning
confidence: 99%
“…The design of twill weave fabric is shown in Figure 20(f). 14,43 The spacing between two yarns is 3 mm and the gaps at the cross-over points are given by H , h , and L . The values were set to H = 0.59 mm, h = 0.65 mm, and L = 0.90 mm.…”
Section: Applicationsmentioning
confidence: 99%
“…According to the literature, heat treatment as a postprocess technique helps to increase crystallinity. 41 Similar to most of the other manufacturing techniques, tensile residual stresses can be formed during the 3D printing process as well. Conducting heat treatment can relieve the tensile residual stresses, generate better interlayer bonds, and increase the mechanical performance of the FDM parts.…”
Section: Fracture Loadsmentioning
confidence: 99%